Integrasi Nilai PAI dalam Menumbuhkan Kesadaran Gizi dan Ketahanan Pangan pada Peserta Didik - Mamba'ur Ridho; M. Mahfudz; Fahmil Fahmil (FKIP UNSULTRA, 2025)
Nutrition awareness and food security are crucial aspects in fostering healthy lifestyles for students. Islamic Religious Education (PAI), as part of the curriculum, has the potential to shape healthy character and behavior through the instillation of spiritual, ethical, and social values. This study uses a literature review approach to examine the role of PAI value integration in enhancing nutrition awareness and food security in students. Literature sources were obtained from scientific journals, academic books, and research reports discussing character education, health, and food security. The study results indicate that the integration of PAI values, such as the principles of halal-haram (permissible and forbidden), justice, simplicity, and social responsibility, can influence students' understanding of the importance of balanced nutrition and sustainable food management. Furthermore, PAI value-based education can foster positive behaviors such as maintaining cleanliness, appreciating food, and reducing food waste. This study emphasizes the need for contextual, creative, and integrated learning strategies between religious and health education. The implications of these findings indicate that PAI teachers have a strategic role in integrating religious values ​​with nutrition education to shape a healthy, nutrition-conscious, and food-security-conscious generation. Further research can explore innovative PAI learning models to strengthen nutrition awareness and food security in elementary and secondary schools.